Analysis of Factors Influencing Difficulties of Occupational Health and Safety Students in Understanding English for Specific Purposes - Ahmad Imam Muzaqi; Dian Safitri (PIJAR: Jurnal Pendidikan dan Pengajaran, 2026)
Proficiency in English for Specific Purposes (ESP) is a professional necessity for Occupational Health and Safety (OHS) practitioners, yet students in Indonesian higher education frequently struggle to develop adequate ESP competencies due to limited exposure to technical English and the absence of contextualized instruction. This study aims to identify and analyze the factors influencing ESP comprehension difficulties among OHS students at Universitas Ibnu Sina Batam, guided by Hutchinson and Waters' (1994) needs analysis framework. A mixed-methods design with a dominant qualitative orientation was employed. Data were gathered via a 30-item questionnaire and semi-structured interviews with 20 purposively selected participants, then analyzed using SPSS and Braun and Clarke’s (2006) thematic framework. Findings reveal that vocabulary limitation, grammatical insecurity, and speaking anxiety are the three primary barriers to ESP acquisition, compounded by a curriculum misalignment between general English instruction and authentic OHS professional demands. These results imply an urgent need to redesign OHS ESP curricula by integrating authentic domain-specific materials, systematic lexical instruction, and communicative task-based approaches aligned with students' career-oriented motivational profiles.